Neto2 Influences on Kainate Receptor Pharmacology and Function. Issue 2 (18th March 2016) - Han, Liwei; Howe, James R.; Pickering, Darryl S.
Abstract: Neuropilin tolloid‐like protein 2 (Neto2) is an auxiliary subunit of kainate receptors (KARs). It specifically regulates KARs, for example slows desensitization and deactivation, increases the rate of recovery from desensitization, promotes modal gating and increases agonist sensitivity. Although the mechanism of Neto2 modulation is still unclear, gain‐of‐function results from the characterization of GluK1–GluA2 chimeras indicate that the GluK1 sequences included in these chimeras (part or all of the TMD and part of the linkers between the TMDs and LBD) play a key role in Neto2 modulation of KAR. In addition, GluK2 M3–S2 linkers and the D1–D1 dimer interface were also recently identified to be important for Neto2 modulation, and some studies suggested that Neto2's N‐terminal regions, LDLa domain and the C‐terminal regions are important for its modulation of KARs. Although more studies are needed to confirm the roles of these domains and to identify all the domains and residues essential for KAR modulation, these results facilitate our understanding of Neto2 modulation at the structural level, which could potentially aid the development of novel therapies for the treatment of diseases that are associated with KARs, for example epilepsies, non‐syndromic autosomal recessive mental retardation, schizophrenia and bipolar disorder.